PSYCHOLOGICAL ASPECTS OF ETHICAL ATTITUDES IN STUDENTS BASED ON AXIOLOGICAL APPROACHES - Amonkhonova Yangilishkhan Abduazizkhan (Journals Park Publishing, 2023)
This article examines the psychological aspects of moral relations among students on the basis of axeological approaches, as well as the issue of the formation of moral relations of young students.
Keywords: Ethical, tutor, advisory, high spirituality, knowledgeable, intelligent, mentally and physically healthy, broad outlook, thinking, Axiological approach, socio-pedagogical value.